Intelligence Strategy on Deradicalization Program to Prevent Acts of Terrorism by Ex-Napiter Network of JAD Group - Ika Veni Anisa; Muhamad Syauqillah (Ridwan Institute, 2023)
The deradicalization programs conducted by BNPT and other stakeholders have been running since the enactment of Undang Undang Nomor 5 Tahun 2018 as a starting point for changing the paradigm of handling terrorism in Indonesia. Terrorism convicts are then assessed, rehabilitated, re-educated, and reintegrated. The program also runs outside the prison for ex-terrorism convicts so that they can back to the community. However, some ex-convicts return to commit terrorist crimes, so preventive measures are needed, especially in term of strategic intelligence measures to prevent this. This paper uses a qualitative approach with case study research. Data collected through interviews as primary data and supported by secondary data derived from official government documents and other journal articles. The case study on the application of the intelligence strategy is explained in the handling of ex-convict P in Solo Raya, in which the intelligence strategy implemented is able to monitor the movement of ex-convicts, help integrate into society and be able to help officers communicate with ex-convicts who are still closed